Physicochemical and adsorption properties of some carbon materials in aqueous solutions - Skorik, Nina A.; Kharlamova, Tamara S.; Vostretsova, E. N.; Dyukarev, N. N. (Protection of metals and physical chemistry of surfaces)
Water dispersions of carbon adsorbents-nanodiamonds of UD-DP and UD-HP-DP types, nanodiamond charge of UDB-A type, C-60 fullerene, nanotubes, and activated carbon-were studied. Some physicochemical properties of their surface (acidity and electrokinetic characteristics) were investigated, and the surface values of pK(a1) were calculated. The data on adsorption of iodine, malic acid, and cationic dyes onto these adsorbents from aqueous and 1 mol/L NaCl solutions were discussed and compared. The dyeadsorption data and the values of the zeta potential and suspension effect indicated a negatively charged surface of UDA-SP nanodiamond within a pH adsorption range from 5.5 to 8.0.